Parent-adolescent communication on sexual and reproductive health among mothers of adolescent girls in Bengaluru urban area: an exploratory study - Serah Rashmi; Rahul Shil; Shreyasee Das (International Journal Of Community Medicine And Public Health, 2026)
Background: Effective parent-adolescent communication about sexual and reproductive health (SRH) promotes accurate knowledge, dispels misconceptions, and encourages healthy behaviors. Early and open discussions can help reduce teenage pregnancy, sexually transmitted infections, and risky sexual behaviors. However, such communication remains limited, necessitating the exploration of barriers to effective SRH discussions between parents and adolescent girls. Methods: This exploratory study was conducted with 100 mothers of adolescent girls residing in urban Bengaluru using convenience sampling techniques. A structured questionnaire, derived from relevant literature, was developed to collect data from the participants. The data was analyzed using SPSS V20.0, employing descriptive statistics, and chi-square tests. Results: Our findings indicate a low level of communication between parents and adolescent girls, with the majority of communication occurring regarding puberty (13.23±4.28) and secondary sexual characteristics changes (8.09±4.07). However, the lowest level of communication was observed in relation to teenage pregnancy (1.37±0.96). Additionally, the study revealed that 16% of parents and adolescent daughters engaged in poor communication, while only 30% exhibited good communication skills. Furthermore, a significant correlation was identified between age and communication levels (r2=0.1019, p=0.04*) educational status (r2=13.97, p=0.05*) family type (r2=15.34, p=0.01**) Source of information (r2=7.13, p=0.03*) at a significance level of 0.05. Conclusions: Our study revealed inadequate parent–adolescent communication on sexual and reproductive health (SRH), influenced by cultural barriers, limited knowledge, and family dynamics. Early, open communication on SRH may strengthen parent-adolescent relationships and reduce unsafe sexual practices.